Ultra-high resolution, multi-scenario, super-elastic inductive strain sensors based on liquid metal for the wireless monitoring of human movement - Mao, Jian (2024)
Flexible strain sensors are an essential component of electronic skin as they are capable of sensing various physiological signals from the human body. They can be used to monitor human health and performance during exercise. However, most currently available strain sensors cannot simultaneously detect both small and large strains on the human skin during movement. In this study, we propose a planar, inductive strain sensor based on liquid metal putty with exceptional elasticity. This sensor can detect both large and small strains: it can measure strains of up to 300% and detect those as low as 0.05% while exhibiting excellent stability (more than 5000 stretch-release cycles) and consistency in terms of variations in inductance (a maximum change of only 1.2%). It also performs well under bending and folding conditions. We also investigated methods to enhance the sensitivity of the sensor under stretching conditions, and used the results to develop a system to monitor signals of human movement based on techniques of wireless transmission and signal processing. This system can capture changes in the magnitude of strain on the skin during human movement, and can be used to monitor various human activities, including respiratory signals, swallowing, and the movements of the joints. Due to these features, the proposed system offers significant potential for use in applications of health and motion monitoring.